(untitled) (Research, Society and Development, 2022)
Among the various production systems, aquaculture recirculation systems (ASR) are due to the high level of technology and optimization of space and water use, resulting in higher productivity rates. Considered an efficient production system, it is noted in the literature that there are few studies between different species and the effects of the environment on their development when cultivated under similar conditions. The objective of the study was to evaluate the zootechnical aspects of juveniles of four fish species: Nile tilapia (Oreochromis niloticus), red tilapia (Oreochromis sp.), pacu (Piaractus mesopotamicus) and silver catfish (Rhamdia quelen) cultivated in RAS and condition factors body weight-length ratio. Twenty-four specimens of each species were used, totaling 96 fish. We verified in the experimental conditions of the present study that all species got used to the culture system evidenced by survival rates and zootechnical indices, and that the cultivation in RAS promotes improvements in the condition factor for nile tilapia, red tilapia and silver catfish, being This is an important indicator of the degree of health.